Mutational Characteristics of Causative Genes in Chinese Hereditary Spherocytosis Patients: a Report on Fourteen Cases and a Review of the Literature - Wang, Dong; Song, Li; Shen, Li; Zhang, Kaihui; Lv, Yuqiang; Gao, Min; Ma, Jian; Wan, Ya; Gai, Zhongtao; Liu, Yi (Frontiers in Pharmacology, 2021)
Background: Hereditary spherocytosis (HS), characterized by the presence of spherocytic red cells in peripheral blood, hemolysis, splenomegaly, jaundice, and gallstones, is a common form of inherited hemolytic anemia (HA). To date, five causative genes associated with HS have been identified, including ANK1, SPTB, SPTA1, SLC4A1, and EPB42. Methods: Clinically suspected patients with HS or undiagnosed HA from 14 Chinese families were enrolled in this study. We presented the patients’ clinical features and identified the causative gene variants in these patients using whole exome sequencing (WES), with 10 novel and four reported mutations in the ANK1 and SPTB genes (seven mutations in ANK1 and seven in SPTB), individually. Then, we reviewed all available literature on Chinese HS patients from 2000 to 2020 in PubMed and Chinese Journals with genetic results and clinical information, to delineate gene mutation spectrum and potential correlation with phenotypes. Results: A total of 158 variants (including 144 in previous reports and 14 in this study) indicated that ANK1 (46%) and SPTB (42%) were the most frequently mutated genes in Chinese HS patients, followed by SLC4A1 (11%) and SPTA1 (1%), while no mutations in EPB42 was reported. Most of the mutations in ANK1 and SPTB were nonsense (26/73 in ANK1 and 32/66 in SPTB) and frameshift (20/73 in ANK1 and 15/66 in SPTB), while missense mutations (14/18) accounted for the majority in SLC4A1. The higher mutation frequency of ANK1 was found in its exon 8, 9, 26, and 28. The majority of mutations in SPTB were located in its exon 13, 15, and 18–30, whereas mutations in SLC4A1 were scattered throughout the entire region of the gene. Conclusion: Our study expanded the mutation spectrum of ANK1 and SPTB. Furthermore, we clarified the mutational characteristics of causative genes by reviewing all available literature on Chinese patients with HS.